Markets as Spaces: An Autoethnography of Women’s Solidarity - R. Duncan M. Pelly; Mariam Abisoye (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales)
Markets are typically depicted as places with an economic or financial rationality, and are described as the genesis of business and entrepreneurship.  Unfortunately, their inner mechanics are oftentimes abstracted away in the pursuit of neat theories.  As a consequence, important insights are lost.  We utilized autoethnography to take a deep dive into markets located in Nigeria.  We discovered that women viewed the market not as a place for profit, but as a space for solidarity-based organizing.  Although participants engaged in business transactions, the primary attraction was the fact that women could exercise independence and mutual aid.  Our story demonstrates the market as a true heterotopia with a different social contract that influenced the values of market participants throughout their lives.  This manuscript is of interest to scholars of entrepreneurship, space, organizing, women’s studies, and solidarity.